P303 Serological assessment of type XVI collagen reflects intestinal strictures in Crohn's disease patients. (16th January 2018) - Mortensen, J H; Olesen, M L; Jensen, C; Willumsen, N; Giuffrida, P; Pinzani, M; Mazza, G; Di Sabatino, A; Karsdal, M A; Manon-Jensen, T
Abstract: Background: Stricturing disease remains one of the biggest complications leading to intestinal resection in Crohn's disease (CD), and affecting 30–50% of patients with CD. Intestinal strictures are caused by fibrosis development, as a result of increased collagen deposition. Intestinal fibroblasts and myofibroblasts are the main effector cells for intestinal fibrosis development and intestinal subepithelial myofibroblasts have shown to produce significantly elevated levels of type XVI collagen in CD patients. Thus, we investigated a novel serum biomarker, quantifying type XVI collagen (C16-C), as a biomarker for intestinal fibrosis in CD patients. Methods: Serum from CD patients ( n = 44) and healthy subjects ( n = 50) was included. The Montreal classification for CD disease behaviour (B1, non-stricturing/non-penetrating: n = 20; B2: stricturing, n = 11; B3: penetrating n = 13) and disease location (L1, ileum: n = 14; L2, colon: n = 5; L3, ileum + colon: n = 25) was applied. The patients were classified as having inactive disease ( n = 20) or active disease ( n = 24) based on the Crohn's disease Activity Index (CDAI) score. Competitive ELISA was applied for the quantification of C16-C in serum from CD patients (total serum samples: n = 94). Results: The biomarker C16-C was significantly elevated in patients with CD compared with healthy donors ( p < 0.001, AUC: 0.81). CD patients with strictures (B2) demonstrated significantly elevated serum levels of C16-C compared with CD patient without strictures (B1 and B3), and healthy donors. Furthermore, the diagnostic accuracy to separate CD patients with strictures (B2) from CD patient without strictures (B1 and B3) was 76% ( p < 0.01, AUC: 0.76) and healthy donors 96% ( p < 0.001, AUC 0.82). In addition, C16-C was also elevated in CD patients with ileum or ileum+colon disease involvement compared with only colon involvement and healthy donors ( p < 0.05). There was no significant difference between patients with active or inactive disease. Conclusions: Our data demonstrate that type XVI collagen can be quantified in serum from CD patients. The biomarker C16-C was significantly associated with stricturing disease phenotype, indicating that this biomarker might be a biomarker for intestinal fibrosis in CD, and may predict intestinal fibrosis development in CD.